Assyriology in Europe. A Report (Council of Europe. Committee for Higher Education and Research. Study Group on Means of Organic Cooperation between the European Universities. CCC/ESR Project 16/22 Rev. English only) - Wiseman, Donald J. (2012)
mimeographed; revised edition of 28:66; cf. Or 36 (1967) 350.